Neuropathic Pain: Unexplored and Significant Relationship With Psoriatic Arthritis and Functional Parameters - Çağrı Ünal ULUTATAR,; Fırat ULUTATAR,; Mehmet Tuncay DURUÖZ, (Archives of Rheumatology, 2020)
Objectives: This study aims to examine the presence of neuropathic pain (NP) in psoriatic arthritis (PsA) and its relationship with functional parameters. Patients and methods: The study included 50 PsA patients (18 males, 32 females; mean age 50 years; range, 27 to 68 years) diagnosed according to The Classification Criteria for Psoriatic Arthritis. NP was assessed with PainDETECT questionnaire (PDQ). Associations of NP with quality of life (QoL), sleep and fatigue were analyzed by filling out the Psoriatic Arthritis Quality of Life (PsAQoL), Pittsburgh Sleep Quality Index (PSQI), and Multidimensional Assessment of Fatigue (MAF) scales, respectively. Group analysis was performed with independent-samples Mann-Whitney U test and Kruskal-Wallis test. Spearman’s rank correlation coefficient (rho) was used for correlations between functional parameters. Results: Mean disease duration of the PsA patients was 90.2±90.8 months]. The number of patients with ambiguous NP was eight (3 males, 5 females) while likely NP was detected in 12 patients (2 males, 10 females). The median scores of visual analog scale-pain, PSQI, PsAQoL and MAF were significantly higher in patients with NP (p<0.05). The correlations between PDQ and other functional parameters were found moderate-strong calculated as follows: PSQI (rho=0.44, p=0.003), MAF (rho=0.42, p=0.005), PsAQoL (rho=0.73, p<0.0001). Conclusion: The existence of NP in PsA is not rare and it has a significant relationship with impaired QoL and sleep disturbances. The assessment of NP in PsA patients is necessary to provide a holistic treatment strategy.